The effect of fiber type on the level of stress concentration created by U-notches in long-fiber composite plates - Turgut, A.; Arslan, N.; Sancaktar, Erol (American Society of Mechanical Engineers (ASME), 1993)
The effect of fiber type on the level of stress concentration created by u-notches were investigated for unidirectional and symmetric cross-ply laminates loaded on or off-axis. The finite element method was used for this purpose utilizing triangular elements under plane stress conditions. Analyses were performed for three different fiber reinforcements of epoxy matrix: glass, graphite and boron. Typical material properties reported in the literature for glass/epoxy, boron/epoxy and graphite/epoxy were used in calculations. The accuracy of the finite element code utilized was first checked by calculating the u-notch stress concentration factors for an isotropic steel plate. © 1993 American Society of Mechanical Engineers (ASME). All rights reserved.
ASME 1993 Design Technical Conferences, DETC 1993 -- 19 September 1993 through 22 September 1993 -- Albuquerque -- 167972
Keywords: Boron; Fibers; Glass; Graphite; Laminated composites; Reliability analysis; Stress analysis; Stress concentration; Cross-ply laminate; Epoxy matrices; Finite element codes; Glass/epoxy; Isotropic steels; Long fiber composites; Plane stress condition; Triangular elements; Finite element method